Information seeking behavior of academicians at Malaysia Institute of Integrative Media/ Mohd Rafiz Salji - Salji, Mohd Rafiz (Fakulti of Information Management, Universiti Teknologi MARA, 2015)
This paper investigated the information seeking behavior of academicians with regards to effort in fulfilling their needs in teaching and improving their learning methods. The survey was carried out at Malaysia Institute of Integrative Media (MIIM), Setiawangsa, Kuala Lumpur. In this case study, questionnaire is the methodology which supported relevant data to collect from those academicians that been chosen as sample at earlier stage. Among the findings of the study; majority of academicians agreed the training skills in information searching is important to the academicians for improving their skills. In searching information, majority preferred Internet as information resource where it easier and quicker accessed information. The majority of academicians felt librarians become preferred person in assisting search information in the library. System failure is common faced by the academicians in searching information and finally academicians tended to use library resources as it valuable to them. Several recommendations proposed; the need to provide information searching skills training, library assistance for academicians should be considered, academicians' should aware towards facilities and resources, advertise the information sources they have and the latest information resources, overcome the internet connection problem and improving the academicians frequency going to the library through various approaches.